Характерні аспекти ситуаційного управління в торговельних організаціях - Мізюк, Б. М.; Ярова, І. М. (Видавництво Львівської політехніки, 2015)
Розкрито зміст, мету та основні завдання здійснення ситуаційного управління в торговельній діяльності, наведено результати аналізу загальних характерних аспектів ситуаційного управління в торговельних організаціях в практичній діяльності керівників різних рівнів, зокрема: обмеженість часу на прийняття обґрунтованих рішень; здатність узгодження регулюючих дій; можливість отримання своєчасної, достовірної і за можливості повної інформації щодо ситуації, яка потребує вирішення. Також розглядаються засоби підвищення ефективності менеджменту підприємства, які ґрунтуються на ситуаційному підході, адже саме він дає можливість керівникам різних ланок та рівнів управління раціонально отримувати позитивні результати. Теоретико-методологічною основою дослідження є теоретичні положення ситуаційного підходу, теорії ймовірності, роботи вітчизняних та зарубіжних вчених із проблем ситуаційного управління. In the article we consider the essence of the process approach, determine the theoretical principles and characteristics of business processes. Some basic types of business processes that arise on the commercial enterprises are shown. We propose operational system of trading enterprise based on the situational approach, which is based on the category of “situation”. The possible problem situations that arise in the course of business on the trade enterprise are considered and certain stagesfor solving and resolving problem situations that mayarise in trade are shown, making it possible to use modeling of business processes. Here we also consider means to enhance the management of the company, based on the situational approach, as it allows managers of different branches and levels of management efficiently obtain positive results. Theoretical and methodological basis of the study are theoretical concepts of situational approach, theory of probability, works of domestic and foreign scholars on issues of situational management. We also analyzed scientific works of domestic and foreign scientists and economists on the application of situational management in enterprises and noted that currently they cover only certain aspects of situational management, but it is not considered as a complex process of bilateral ties, there are no systematic studies on the use of situational management in trading organizations. In the process of study the following methods were used, in particular: inductive, deductive ones – while collecting, organizing and processing of information; theoretical generalization – in the process of uncovering the nature and main characteristics of situational management. In conclusion the theoretical generalizations about key aspects of situational management on the trade enterprises was made. Results of the study show that the practical activities of the leaders of different levels of trade enterprises showed that the main criteria of situational management is to limit the time for performing management cycle, consistency of management functions and information support for decision-making. We offer prospects for further studies, which show that despite the urgent need for situational approach in the management of trade enterprises and organizations, currently there is nosufficient systematic research on this issue in scientific literature.
Construction of the operating systems in business process management on the situational approach
Keywords: управління; ситуаційне управління; торгові організації і підприємства; управлінський цикл; управлінські функції; прийняття рішень; management; case management; оperational management; situation; process; business process; trading enterprises; situational approach; accounting; analysis; control